Penerapan Pendekatan Personal Selling dalam Promosi Perpustakaan Institut Teknologi Bandung melalui Program Duta Kampus ITB - Azhim Zulikha; Nuning Kurniasih; Saleha Rodiah (Universitas Sebelas Maret Library, 2025)
Institut Teknologi Bandung (ITB) Library provides various services, yet many students do not utilize them optimally due to limited awareness and engagement. To address this, a personal selling approach was implemented through the ITB Campus Ambassador program. This study aims to analyze how personal selling is applied by Campus Ambassadors in promoting library services, focusing on strategies used, forms of involvement, and the impact on student awareness and participation. This research adopts a qualitative method with a case study approach. Data were collected through interviews, observation, and documentation. The findings show that ITB Campus Ambassadors serve in multiple roles: as speakers, moderators/MCs, content creators, and tour guides. In these roles, they deliver promotional messages in a communicative and personal manner across various platforms, both direct and digital. With relatable peer characteristics, appropriate communication style, and social influence, they build stronger connections and enhance the effectiveness of the library’s promotional messages. These findings suggest that Campus Ambassadors act as effective personal selling agents, bridging communication between the library and students while strengthening the library's image on campus.